Cognitive biases and decision making (International Journal of Environmental Sciences, 2025)
The objective is to identify cognitive biases in managers when making decisions. A bibliographic review of the main postulates of cognitive psychology was carried out, part of the contributions of March and Simón, authors of the cognitive school of organization. The descriptive, cross-sectional and intra-individual study, the sample of 58 managers from the city of Riobamba, Ecuador, in middle age (age 25-35 years), women 28%, men, 72%. A 12-item survey was used to identify (10 biases): recency, anchorage, confirmation, halo, excessive optimism, availability, planning, group, sunk cost, possession effect, a high percentage confirming the use of these is evident. cognitive biases in managers' decision making; In addition, it was identified that there were gender differences in cognitive biases when making decisions: women are analytical and less risky in their decisions, while men accept greater risk and uncertainty when making decisions, this study will allow in Future research will make a comparison of the ages of the managers; Cognitive biases allow us to understand and explain the behavior of managers in highly complex situations in managerial functions.